Suicide in Ireland: The influence of alcohol and unemployment - Brendan M. Walsh; Dermot Walsh (University College Dublin, UCD School of Economics, 2010)
In this paper we model the behaviour of the Irish suicide rate over the period 1968-2009 using the unemployment rate and the level of alcohol consumption as explanatory variables. It is found that these variables have significant positive effects on suicide mortality in several demographic groups. Alcohol consumption is a significant influence on the male suicide rate up to age 64. Its influence on the female suicide rate is not as well-established, although there is evidence that it is important in the 15-24 and 25-34 age groups. The unemployment rate is also a significant influence on the male suicide rate in the younger age groups. The behaviour of suicide rates among males aged 55 and over and females aged 25 and over is largely unaccounted for by our model. These broad conclusions hold when account is taken of a structural break in the 1980s, with the response to unemployment being greater in the earlier period and that to alcohol greater in the later period. The findings suggest that higher alcohol consumption played a major role in the increase in suicide mortality among young Irish males between the late 1960s and the end of the century. In the early twenty first century a combination of falling alcohol consumption and low unemployment led to a marked reduction in suicide rates, although there is some evidence that the suicide rate is being increasingly under-reported in recent years. The recent rise in the suicide rate may be attributed to the sharp increase in unemployment, especially among males, but it has been moderated by the continuing fall in alcohol consumption. Some policy implications of the findings are discussed.
hdl:10197/2669
Keywords: 330